Determination of Source Terms in Diffusion and Wave Equations by Observations After Incidents: Uniqueness and Stability (CSIAM Transactions on Applied Mathematics, 2023)
We consider a diffusion and a wave equations$$∂^k_tu(x,t) =∆u(x,t)+μ(t)f(x), x∈Ω, t>0, k=1,2$$with the zero initial and boundary conditions, where $Ω ⊂\mathbb{R}^d$ is a bounded domain. We establish uniqueness and/or stability results for inverse problems of determining $μ(t), 0